2019
DOI: 10.1177/1065912919878264
|View full text |Cite
|
Sign up to set email alerts
|

Deep Determinants of Corruption? A Subnational Analysis of Resource Curse Dynamics in American States

Abstract: Drawing on comparative resource curse literature and American literature on the determinants of corruption, we argue that the impact of natural resource extraction on corruption outcomes is state-dependent. That is, in environments where corruption is already high, natural resource windfalls allow political actors and economic elites to take advantage of state brokerage, further increasing corruption. However, in previously less-corrupt states, increased natural resource extraction will not induce corruption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Li and Morrisetal [29,30] concluded that resource-based areas' economic structure is unreasonable; the "locking" and "crowding out" effects hindered the upgrading of the local industrial network. Goel, Zhan, and Tyburski [31][32][33] tested whether the corruption caused by abundant resources is the root cause of the resource curse. However, not all countries have the same situation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li and Morrisetal [29,30] concluded that resource-based areas' economic structure is unreasonable; the "locking" and "crowding out" effects hindered the upgrading of the local industrial network. Goel, Zhan, and Tyburski [31][32][33] tested whether the corruption caused by abundant resources is the root cause of the resource curse. However, not all countries have the same situation.…”
Section: Literature Reviewmentioning
confidence: 99%